Attempts to Improve Lipophilic Drugs' Solubility and Bioavailability: A Focus on Fenretinide - Silvana Alfei; Guendalina Zuccari (MDPI AG, 2024)
The development of numerous drugs is often arrested at clinical testing stages, due to their unfavorable biopharmaceutical characteristics. It is the case of fenretinide (4-HPR), a second-generation retinoid, that demonstrated promising in vitro cytotoxic activity against several cancer cell lines. Unfortunately, response rates in early clinical trials with 4-HPR did not confirm the in vitro findings, mainly due to the low bioavailability of the oral capsular formulation that was initially developed. Capsular 4-HPR provided variable and insufficient drug plasma levels attributable to the high hepatic first-pass effect and poor drug water solubility. To improve 4-HPR bioavailability, several approaches have been put forward and tested in preclinical and early-phase clinical trials, demonstrating generally improved plasma levels and minimal systemic toxicities, but also modest antitumor efficacy. The challenge is thus currently still far from being met. To redirect the diminished interest of pharmaceutical companies toward 4-HPR and promote its further clinical development, this manuscript reviewed the attempts made so far by researchers to enhance 4-HPR bioavailability. A comparison of the available data was performed, and future directions were proposed.